Leadership in elephants: the adaptive value of age - McComb, Karen; Shannon, Graeme; Durant, Sarah M; Sayialel, Katito; Slotow, Rob; Poole, Joyce; Moss, Cynthia (Proceedings of the Royal Society. B, Biological sciences, 2011)
The value of age is well recognized in human societies, where older individuals often emerge as leaders in tasks requiring specialized knowledge, but what part do such individuals play in other social species? Despite growing interest in how effective leadership might be achieved in animal social systems, the specific role that older leaders may play in decision-making has rarely been experimentally investigated. Here, we use a novel playback paradigm to demonstrate that in African elephants (Loxodonta africana), age affects the ability of matriarchs to make ecologically relevant decisions in a domain critical to survival-the assessment of predatory threat. While groups consistently adjust their defensive behaviour to the greater threat of three roaring lions versus one, families with younger matriarchs typically under-react to roars from male lions despite the severe danger they represent. Sensitivity to this key threat increases with matriarch age and is greatest for the oldest matriarchs, who are likely to have accumulated the most experience. Our study provides the first empirical evidence that individuals within a social group may derive significant benefits from the influence of an older leader because of their enhanced ability to make crucial decisions about predatory threat, generating important insights into selection for longevity in cognitively advanced social mammals.